Infections in breast implants: a review with a focus on developing countries - Rubino, Corrado; Brongo, Sergio; Pagliara, Domenico; Cuomo, Roberto; Abbinante, Giulia; Campitiello, Nicola; Santanelli, Fabio; Chessa, Daniela (The Journal of Infection in Developing Countries, 2014)
The risk of surgical site infection is always present in surgery; the use of prosthetic materials is linked to an increased possibility of infection. Breast augmentation and breast reconstruction with implants are gaining popularity in developing countries. Implant infection is the main complication related to breast aesthetic and reconstructive surgery. In the present paper, we reviewed the current microbiological knowledge about implant infections, with particular attention to risk factors, diagnosis, clinical management, and antibiotic prophylaxis, focusing on reports from developing countries. After breast aesthetic surgery, up to 2.9% of patients develop a surgical site infection, with an incidence of 1.7% for acute infections and 0.8% for late infections. The rate of surgical site infection after post-mastectomy breast reconstruction is usually higher, ranging from 1% to 53%. The clinical features are not constant, and bacterial culture with antibiogram is the gold standard for diagnosis and for identification of antibiotic resistance. While waiting for culture results, empiric therapy with vancomycin and extended-spectrum penicillins or cephalosporins is recommended. Some patients require removal of the infected prosthesis. The main methods to bring down the risk of infection are strict asepsis protocol, preoperative antibiotic prophylaxis, and irrigation of the surgical pocket and implant with an antibiotic solution.